Ecological conditionality of cancer morbidity in the Laksky region of Daghestan republic - A. G. Gasangadjieva; E. G. Abdurakhmanova; A. G. Magomedova (Юг России: экология, развитие)
The condition of the components of the Inner Daghestan regions biota is investigated (on the Laksky region of Daghestan republic). There are revealed the features of oncological morbidity in the region. The dependence of heavy metals in the soil and drinking-water basins on the territory of this region is stated.